OPTIMALISASI STRATEGI KOMUNIKASI DAN MANAJEMEN RELATIONS DI KEMENTERIAN PERTANIAN DALAM IMPLEMENTASI PENTINGNYA SATU DATA TERPADU UNTUK PEMBANGUNAN BERKELANJUTAN DI INDONESIA - Prasetyo, Nurhadi; Prihantoro, Edy (Jurnal Spektrum Komunikasi, 2024)
Satu Data Indonesia (SDI) is a government data governance policy that aims to support the availability of data that is accurate, up-to-date, integrated, accountable and easily accessible and shared between government agencies to support development planning, monitoring and evaluation towards an advanced Indonesia. This policy is contained in Presidential Regulation no. 39 of 2019 concerning One Data Indonesia and is expected to improve data governance. The purpose of this research is to analyze the implementation of effective public communication and relationship management strategies in increasing the Ministry of Agriculture's awareness of the importance of One Data Indonesia Towards Advanced Indonesia. The method used in this research is qualitative with a case study approach. Researchers will conduct in-depth interviews with Ministry of Agriculture officials. The Ministry of Agriculture has shown a strong commitment to the implementation of SDI through initiatives and regulations that have been issued. The Ministry of Agriculture has launched the Agricultural Data Portal as an efficient and comprehensive form of public communication in raising awareness of the importance of One Data Indonesia Towards a Developed Indonesia.